Allergens produce serine proteases‐dependent distinct release of metabolite DAMPs in human bronchial epithelial cells. Issue 2 (28th December 2017) - Ramu, S.; Menzel, M.; Bjermer, L.; Andersson, C.; Akbarshahi, H.; Uller, L.
Summary: Background: The respiratory epithelium is a major site for disease interaction with inhaled allergens. Additional to IgE‐dependent effects, allergens contain proteases that may stimulate human bronchial epithelial cells (HBECs) through protease‐activated receptors, causing the release of mediators important in driving Th2‐mediated immune responses. Objective: We aimed to investigate whether different allergens induce metabolite DAMPs such as ATP and uric acid (UA) release in HBECs. Methods: HBECs (BEAS‐2B cell line) were exposed to different allergen extracts; house dust mite (HDM), Alternaria alternata, Artemisia vulgaris and Betula pendula and UA, ATP, IL‐8 and IL‐33 release were measured. Allergen extracts were heat‐inactivated or pre‐incubated with serine (AEBSF) or cysteine (E64) protease inhibitors to study the involvement of protease activity in ATP, UA and IL‐8 release. HDM‐induced release of UA was studied in a mouse model of allergic inflammation. Results: All allergens caused dose‐dependent rapid release of ATP and IL‐8, but only HDM induced UA release from HBECs. HDM also caused release of UA in vivo in our mouse model of allergic inflammation. ATP release by all 4 allergen extracts was significantly reduced by heat‐inactivation and by serine protease inhibitors. Similarly, the HDM‐induced UA release was also abrogated by heat‐inactivation of HDM extract and dependent on serine proteases. Furthermore, allergen‐induced IL‐8 mRNA expression was inhibited by serine protease inhibitors. Conclusions and Clinical Relevance: ATP was released by all 4 allergens in HBECs supporting the role of ATP involvement in asthma pathology. However, HDM stands out by its capacity to cause UA release, which is of interest in view of the proposed role of UA in early initiation of allergic asthma. Although serine proteases may be involved in the activity of all the studied allergens, further work is warranted to explain the differences between HDM and the other 3 allergens regarding the effects on UA release.